2020
DOI: 10.1007/s00401-020-02153-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence in Britain of abnormal prion protein in human appendices before and after exposure to the cattle BSE epizootic

Abstract: Widespread dietary exposure of the population of Britain to bovine spongiform encephalopathy (BSE) prions in the 1980s and 1990s led to the emergence of variant Creutzfeldt-Jakob Disease (vCJD) in humans. Two previous appendectomy sample surveys (Appendix-1 and -2) estimated the prevalence of abnormal prion protein (PrP) in the British population exposed to BSE to be 237 per million and 493 per million, respectively. The Appendix-3 survey was recommended to measure the prevalence of abnormal PrP in population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…Despite a relatively limited number of identified clinical cases ( n = 231), the most recent epidemiological studies indicated that 1 out 2000 people in the UK could carry the vCJD agent (as judged by the presence of abnormal prion protein detected by immunohistochemistry in lymphoid follicles in the appendix) and that the exposure period to BSE agent in the UK could have largely exceeded the period initially considered to be at risk (i.e. the 1985–1996 period) [ 22 , 23 ]. Over the 25 years since the emergence of vCJD only five instances that are a likely consequence of iatrogenic vCJD transmission have come to light, all in the UK and all associated with blood and blood-products [ 36 , 37 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a relatively limited number of identified clinical cases ( n = 231), the most recent epidemiological studies indicated that 1 out 2000 people in the UK could carry the vCJD agent (as judged by the presence of abnormal prion protein detected by immunohistochemistry in lymphoid follicles in the appendix) and that the exposure period to BSE agent in the UK could have largely exceeded the period initially considered to be at risk (i.e. the 1985–1996 period) [ 22 , 23 ]. Over the 25 years since the emergence of vCJD only five instances that are a likely consequence of iatrogenic vCJD transmission have come to light, all in the UK and all associated with blood and blood-products [ 36 , 37 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has been reported that transgenic mice carrying a pathogenic mutation of the PRNP gene can lead to spontaneous prion disease [41,42]. In addition, a recent study has been reported that PrP Sc were also detected in healthy people, who have not been diagnosed with prion diseases [43]. On the basis of these studies, we postulated that cancer patients carrying pathogenic somatic mutation of the PRNP gene may produce a basal level of PrP Sc in peripheral tissues and may not be diagnosed with prion disease.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the detection of infectivity in lymphoreticular tissues during the long asymptomatic incubation periods [ 47 , 128 ] and reports of transfusion-transmission of vCJD infectivity from asymptomatic vCJD patients [ 124 ], questioned the numbers of the UK population harboring asymptomatic vCJD infection and the possible risk of further secondary human transmission via blood transfusion and potentially from surgery. In the absence of a blood-based assay for vCJD, three retrospective studies investigating PrP accumulation in formalin-fixed appendix tissue were undertaken to address these concerns [ 130 , 131 , 132 , 133 ]. This followed the observation of PrP positivity in appendix tissue removed from two patients that went on to develop clinical vCJD eight months and two years after their appendectomies [ 134 ].…”
Section: Prion Diseasesmentioning
confidence: 99%
“…This followed the observation of PrP positivity in appendix tissue removed from two patients that went on to develop clinical vCJD eight months and two years after their appendectomies [ 134 ]. Positive staining for the prion protein was reported in appendix specimens examined in all three studies and has provided a current estimated prevalence of asymptomatic vCJD infection in the UK of approximately 1 in 2000 of the population [ 131 , 133 ]. Genetic analysis of the positive appendix samples showed PrP accumulation in appendix specimens from all possible PRNP codon 129 genotypes [ 133 , 135 ], thus supporting data from experimental animal studies that showed all three PRNP codon 129 genotypes are susceptible to vCJD infection but may be subject to lengthy incubation periods [ 92 ].…”
Section: Prion Diseasesmentioning
confidence: 99%